Arduino based Controller for the Smart Assistive Mobility Hardware - Lengvenis, P.; Maskeliunas, R.; Raudonis, V. (Elektronika ir Elektrotechnika, 2012)
The main goal of this work is the development of Arduino microcontroller based integral solution for the smart, assistive mobility hardware. The paper presents schematics of device control and electrics, the control logic, the power regulation chain model and affiliated calculate efficiency parameters. The overall experimental investigation of real-life performance of our Arduino model proved quite successful. The added power regulator allowed achieving the stable outputs (±0.001V) to mimic the original controller. The deviation in trajectory compared to the ideal model was small (< 10 %) and can be further reduced by doing micro corrections. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2812